THE INFLUENCE OF ACADEMIC SUPERVISION BY THE PRINCIPAL IN IMPLEMENTING DEEP LEARNING FOR TEACHERS AT MTS AZ-ZAHROH SENDANG REJO - Sri Warningsih; Nathanael Sitanggang; Aman Simare-mare; Irsan Rangkuti; Arif Rahman (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study investigates the influence of principal-led academic supervision on the implementation of deep learning-based instruction among teachers at MTs Az-Zahroh Sendang Rejo. Using a quantitative correlational method, data were collected through a structured questionnaire comprising 30 items distributed to all teachers as respondents. The academic supervision variable included indicators such as planning, implementation, feedback, and evaluation-follow-up, while deep learning was measured using Michael Fullan’s 6Cs: character, citizenship, collaboration, communication, creativity, and critical thinking. Descriptive analysis revealed that academic supervision was generally perceived positively, particularly in feedback and planning aspects. However, the evaluation and follow-up components scored lower. In contrast, deep learning implementation showed moderate results across most indicators, with creativity and critical thinking receiving the lowest percentages. Regression analysis using SPSS showed a strong positive correlation (R = 0.962) between academic supervision and deep learning, with 92.5% of the variance in deep learning practices explained by supervision. The findings indicate that effective academic supervision significantly enhances teachers’ ability to implement deep learning. The study recommends strengthening the principal’s role as an instructional leader to promote deep learning competencies more holistically and sustainably.